PENGARUH UKURAN DEWAN DIREKSI, UKURAN DEWAN KOMISARIS, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR : board of directors, board of commissioners, company size, return on assets (ROA). - Suparman, Petrus (GEMA EKONOMI, 2020)
This study aims to examine and prove the effect of board size, board size, and company size on the financial performance of manufacturing companies. This study uses a quantitative approach with multiple linear regression analysis models. This study used a purposive sampling method, namely the panyampelan method based on certain criteria. The number of samples used is 30 samples of financial statements for the 2015-2018 period. The results of this study are the size of the board of directors has a negative effect on the financial performance of manufacturing companies, the size of the board of commissioners partially has a positive effect on the financial performance of manufacturing companies, the size of the board of directors and the size of the company partially have a negative effect on the financial performance of manufacturing companies. Meanwhile, simultaneously the size of the board of directors, size of the board of commissioners and company size have a positive effect on the financial performance of manufacturing companies.